Some considerations on the accumulation of ice on the balloon fabric - MUKHERJEE, A. K.; RAKSHIT, D. K. (MAUSAM, 1964)
Data of Kachare al. (1957) for up and down movements of radiosonde balloons due to collection of snow on balloon fabric were examined. It was found that accumulation of ice was related 10 rate of ascent of the balloon. It was also found that the rate of descent was in some way related to the rate of previous ascent. In general height descended increased with increase in rate of descent and also with the increase in the amount of snow accumulated; but there were a few exceptions to this observation. Similarly, load in balloon in general increased during successive ascents; here also there were two exceptions. To understand the process of removal of ice amounts of melting of ice on balloon surface were calculated. It was found that in some cases amount of ice that could melt was less than the amount that was removed indicating some ice was removed without melting. To explain all the observations a mechanism of wetting of balloon surface, accumulation of ice on and its removal from fabric have been proposed. It has been shown that the ice accumulates non-uniformly and though In general is removed by melting, sometimes ice is peeled off from the balloon surface when it descends getting warm and shrinking during the course.